Lakotacrinus brezinai n. gen. n. sp., a new stalked crinoid from cold methane seeps in the Upper Cretaceous (Campanian) Pierre Shale, South Dakota, United States. (5th July 2016) - Hunter, Aaron W.; Larson, Neal L.; Landman, Neil H.; Oji, Tatsuo
Abstract: Despite a rich and varied record, Mesozoic stalked crinoids are relatively rare in the Western Interior Seaway of North America compared to those found in Northern Europe. A unique example of Mesozoic stalked crinoid is described from cold methane seeps (hydrocarbon seep mounds also called "tepee buttes") from the Upper Cretaceous (upper Campanian) of the Northern Great Plains of the United States; the first crinoids to be described from such an environment. The Late Cretaceous Western Interior Seaway has never before yielded any identifiable stalked crinoid remains. Nevertheless, there have been significant studies on both free living and stalked crinoids from other locations in the Upper Cretaceous of North America that provide a good basis for comparison. Lakotacrinus brezinai n. gen. n. sp. is characterized by a tapering homeomorphic column with through-going tubuli, lacking any attachment disc. The arms are unbranched and pinnulate, with muscular and syzygial articulations. The unique morphology of the column justifies the establishment of Lakotacrinidae new family. A new suborder Lakotacrinina n. subord., is also proposed as there exists no corresponding taxon within the Articulata that can accommodate all the characteristics of this new genus. This new crinoid shares many features with other members of the articulates, including bathycrinids, bourgueticrinids and guillecrinids within the Order Comatulida, as currently defined in the revised Treatise of Invertebrate Paleontology. Reconstructing the entire crinoid using hundreds of semi-articulated and disarticulated (well preserved) fossils, reveals a unique paleoecology and functional morphology specifically adapted to living within this hydrocarbon seep environment.